Research on Development Problems and Transformation Strategies of Platform-type Internet Enterprises Based on Porter’s Five Forces and SWOT Model: A Case Study of 58. Com Human Resource Service Business Module - Xu, Xinyuan; Zhang, Yihan (Transactions on Economics, Business and Management Research, 2024)
The platform Internet enterprises represented by 58. Com have occupied a large market share due to their early entry into the market. In the face of the rise of mobile Internet and the rise of many emerging industries, some enterprises are faced with problems such as uneven information quality, single profit model, and difficult to guarantee user privacy. They no longer have comparative advantages when competing for market share, and gradually lag behind the development of The Times. This paper uses Porter’s Five Forces model analysis, SWOT analysis and other methods to explore the further development and transformation of the platform Internet enterprises taking 58. Com as an example. Due to the simple review process of mobile Internet platforms, complex Internet environment and the existence of information leakage, platform Internet companies should strengthen the review process, establish an enterprise ecosystem, strengthen technical supervision and improve user privacy protection policies, so as to obtain a new development peak in the market battle in the new era.